Kontestasi Pemaknaan Kepemimpinan Publik di PILGUB DKI: Perspektif Relasi Kuasa - Zauhair Al Fawwaz, Fajriz; Musthafa, Adib Khairil (Tafáqquh: Jurnal Penelitian Dan Kajian Keislaman, 2024)
This article explains about the hegemony of MUI related to the blasphemy case in the 2017 DKI Pilgub which is based on surah al-Maidah verse 51, there are various opinions that give birth to community polarization. Therefore, this article will answer the question of how the relevant meaning today of the word "Auliya" in surah al-Maidah verse 51. This article uses Michel Foucault's theory of power relations related to the knowledge produced by MUI. The result of this discussion is that there are opinions of interpreters who do not allow non-Muslim leaders as Muslim leaders, such as Ibn Kathir and Sayyid Qutb. Some others allow it, such as Ibn Taymiyah, Muhammad Abduh and Ashgar Ali Engineer and Sahiron Syamsuddin. The MUI's "Religious Opinion and Position" states that Basuki Tjahaya Purnama has blasphemed and cannot lead the Muslim community. Meanwhile, there is a counter from Kiai Muda Ansor Youth Movement and Sahiron Samsuddin's interpretation with ma'na cum maghzanya approach that views the interpretation of the word "Áuliya" verse 51 surah Al-Maidah from the side of the agreement that has been agreed upon then broken by one of them and is far different from MUI's "Opinion and Religious Attitude" especially that the interpretation of this verse is not about leadership, but the breaking of promises.